1999
DOI: 10.1099/0022-1317-80-4-1009
|View full text |Cite
|
Sign up to set email alerts
|

Use of the baculovirus system to assemble polyomavirus capsid-like particles with different polyomavirus structural proteins: analysis of the recombinant assembled capsid-like particles.

Abstract: The genes encoding the structural proteins (VP1, VP2 and VP3) of murine polyomavirus were cloned into the p2Bac dual multiple cloning site vector, individually or jointly, and the corresponding proteins were expressed in Spodoptera frugiperda (Sf9) insect cells by cotransfecting Sf9 cells with the constructed vector and the linear DNA of Autographa californica multiple nuclear polyhedrosis virus (AcMNPV). Recombinant capsid-like particles could be purified 5 days post-infection from Sf9 cells infected with AcM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Py-VLPs expressed in insect cells frequently contain cellular DNA (1,20). Analysis of the partially purified Py-VLPs derived from VP1/wt, VP1/HI-FLAG, and VP1/EF-uPA(1-60)/ HI-FLAGϩVP1/HI-FLAG by agarose gel electrophoresis after DNase I treatment showed that they contained ϳ5 kb of FIG.…”
Section: Resultsmentioning
confidence: 99%
“…Py-VLPs expressed in insect cells frequently contain cellular DNA (1,20). Analysis of the partially purified Py-VLPs derived from VP1/wt, VP1/HI-FLAG, and VP1/EF-uPA(1-60)/ HI-FLAGϩVP1/HI-FLAG by agarose gel electrophoresis after DNase I treatment showed that they contained ϳ5 kb of FIG.…”
Section: Resultsmentioning
confidence: 99%
“…The combined abilities of the Py VP1 protein to self-assemble into virus-like particles (VLPs) and to nonspecifically interact with homologous or heterologous DNA has led to VP1 VLPs being proposed as potential vectors for gene therapy (1,35,51). VLPs efficiently transfer DNA and allow its expression in mammalian cells in vitro and in vivo with a wide tissue distribution (13,22,47).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, pseudocapsids made from VP1 and VP2 are more effective in blocking interaction of virus with the cell, than those composed of VP1 alone. 39 Thus, a particular function may be missing from pseudocapsids, which, if replaced, could restore the efficiency of transfer to levels nearer that achieved with viruses.…”
Section: % Triton X 100 and Pseudocapsid Uptake Followed In Cells Bymentioning
confidence: 99%